Sexual Risk Behavior: A Perilous Journey By Unmarried Youth Of District Dehradun, Uttarakhand - Jain, Rajnish; Semwal, Jayanti; Vyas, Shaili; Srivastava, Malini (Indian Journal of Community Health, 2018)
Background: Sexual health is an integral part of overall health and well-being and determination of sexuality of the youth is an important milestone in understanding their behavior, associated risks and outcomes. The declining age at puberty and increasing age at marriage has created a longer growing period in which youth may engage in sexual health risk behaviors. This research focuses attention on estimation and involvement of the most dynamic & valuable segment of a nation’s population towards sexual risk behaviors. Aims & objectives: The aim of this study is to find out the prevalence and determinants of sexual health risk behaviors amongst youth in District Dehradun. Material and methods: It was a cross-sectional study conducted over a period of 06 months in rural and urban area of District Dehradun. The study surveyed 1800 male youth aged 15-24 years using a self-administered questionnaire (YRBSS & Big five inventory). After collection, the data was entered using the SPSS software and analyzed using SPSS and Microsoft Excel 2010. Results: Out of 1800 participants, 19% were found to be at risk of sexual health risk behavior and reported having had sex. Out of these 342 at-risk, 43.5% accepted involving in sexual activity even before adulthood, 31% reported having multiple sexual partners and 21.1% accepted not using condoms. Place of residence and personality trait were found to be important determinants of sexual health risk behaviors. Conclusion: Our study documented the high prevalence of sexual risk behavior among male youth of rural and urban area of District Dehradun.